Successful recovery of COVID‐19 pneumonia in a renal transplant recipient with long‐term immunosuppression. Issue 7 (31st March 2020) - Zhu, Lan; Xu, Xizhen; Ma, Ke; Yang, Junling; Guan, Hanxiong; Chen, Song; Chen, Zhishui; Chen, Gang
Abstract : The current outbreak of Coronavirus Disease 2019 (COVID‐19) has raised great concern worldwide, but its impact on transplant recipients is unknown. We report here the clinical features and therapeutic course of the first reported renal transplant recipient with confirmed COVID‐19 pneumonia. This is a 52‐year‐old man who received kidney transplantation 12 years ago. His overall clinical characteristics (symptoms, laboratory examinations, and chest CT) were similar to those of non‐transplanted COVID‐19 patients. Following a treatment regimen consisting of reduced immunosuppressant use and low dose methylprednisolone‐based therapy, the COVID‐19 pneumonia in this long‐term immunosuppressive patient was successfully recovered. This effectively treated case has reference value for the future treatment of other transplant patients with COVID‐19 pneumonia. Abstract : This study reports a renal transplant recipient who recovered from COVID‐19 pneumonia after a treatment regimen consisting of reduced immunosuppressant use and low‐dose methylprednisolone‐based therapy.